The Impact of Probiotics on Clinical Symptoms and Peripheral Cytokines Levels in Parkinson’s Disease: Preliminary In Vivo Data - Luca Magistrelli; Elena Contaldi; Annalisa Visciglia; Giovanni Deusebio; Marco Pane; Angela Amoruso (Brain Sciences)
Introduction. Previous studies have shown that probiotics have positive effects on both motor and non-motor symptoms in Parkinson’s disease (PD). Additionally, in preclinical settings, probiotics have demonstrated the ability to counteract neuronal loss and alpha-synuclein aggregation, important pathological hallmarks of PD. Notably, preliminary in vitro studies have revealed the immunomodulatory properties of probiotics. This study aims to evaluate the impact of probiotics on symptoms and peripheral cytokines levels in PD patients compared to placebo. Methods. Patients were enrolled and blindly randomized to receive either active probiotics (comprising Bifidobacterium animalis subsp. lactis BS01 LMG P-21384, Bifidobacterium longum BL03 DSM 16603, Bifidobacterium adolescentis BA02 DSM 18351, Fructo-oligosaccharides and Maltodextrin-Group A) or placebo (Maltodextrin-Group B). Clinical evaluations and plasma levels cytokines (TNF-α, IFN-γ, IL-6, and TGF-β) were also assessed at enrollment and after 12 weeks. Anti-parkinsonian therapy remained stable throughout the study. Results. Forty PD patients were recruited. After 12 weeks, Group A showed significant improvement in motor symptoms (UPDRS III: 13.89 ± 4.08 vs. 12.74 ± 4.57, p = 0.028) and non-motor symptoms (NMSS: 34.32 ± 21.41 vs. 30.11 ± 19.89, p = 0.041), with notable improvement in the gastrointestinal sub-item (3.79 ± 4.14 vs. 1.89 ± 2.54, p = 0.021). A reduction of IFN-γ levels was observed in both groups, but group A also showed a significant decrease in IL-6 and a slight increase in the anti-inflammatory cytokine TGF-β. Conclusions. Our data suggest that probiotics may modulate peripheral cytokines levels and improve clinical symptoms in PD patients. Probiotics may, therefore, represent a valuable adjunctive therapy to conventional anti-parkinsonian drugs.